Previous Studies on The Impact of Online Education in EFL and ESL contexts - Hashemi, Ali (Technium Social Sciences Journal, 2021)
Unexpected Covid-19 global outbreak in the world, has had a broad effect on people’s life and their daily activities. Globally, education at all levels as an important part of people’s lives has been influenced due to the pandemic of Covid-19. Teachers and students, as the key role players of education, have felt the impacts of online education both negatively and positively. Hence, this article aimed to collect and analyze perception of EFL and ESL learners and teachers toward online education during Covid-19 pandemic and put effort into finding some solutions for the negative effects of online learning. The selected previous studies about this topic were chosen from different published articles in multiple countries in EFL and ESL context. As a result, the article found that online education had a negative impact on the majority of the learners and teachers, although there were some positive impacts too.